The potential relationship between EasyNAT system Tt values and Cobas z480 Ct values in the detection of SARS-Cov-2 - Zheng, Lu-Qing; Wang, Qing-Yong (Practical laboratory medicine, 2024)
This study aimed to evaluate the potential relationship between the time threshold (Tt) values of a commercial EasyNAT system, which is based on cross priming amplification (CPA) technology, and the cycle threshold (Ct) values of the Cobas z480 analyzer, which is based on a real-time fluorescence polymerase chain reaction (PCR) method, in the detection of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) from oropharyngeal swabs. Design and Methods: Data were retrospectively collected from a clinical laboratory between December 4, 2022 and July 1, 2024. A total of 277 EasyNAT-positive samples (Tt values from 3.83 to 29.5) were simultaneously investigated using the Cobas z480 analyzer (Ct values from 10.74 to 38.78). The concordance rate between the two systems was 100 %. Among the positive samples, the mean and maximum PCR Ct values of O and N genes increased in line with increasing Tt values of the left and right amplification areas of the EasyNAT system. The maximum Ct values of the O or N gene determined by the Cobas z480 analyzer were no more than 29.52 when the Tt values of the left or right amplification areas of the UC0116 analyzer were no more than 6. The safe, simple, fast, accurate, and automatic EasyNAT system used in conjunction with a PCR system might be a better choice for the detection of SARS-CoV-2 in hospitals, especially in settings without sophisticated PCR facilities. The Tt value (≤6) of the EasyNAT system can be a reference index for estimating the maximum Ct value (29.52) in SARS-CoV-2-positive samples.